Reflections on Sustainability and Resilience in the NGO Sector. Issue 3 (3rd July 2019) - Appe, Susan
Abstract : This reflection outlines the origins of the terms "sustainability" and "resilience" and the meanings they have when applied to the nongovernmental sector. The use of specific jargon and language for nongovernmental organizations (NGOs) is common in academic scholarship, policy debates, and popular media. The reflection contributes a conceptual inquiry to understanding these increasingly used terms in the NGO sector. The article begins with the assumption that language and the narrative forms it takes have been important in the social sciences and to public administration theory building specifically. Comparative examples of the use of "sustainability" and "resilience" in scholarship and practice are presented to demonstrate the tension created for the NGO sector as these terms tend to have underpinnings related to the neoliberal project and individualism, ideals that might challenge the goals sought by NGOs and hinder objectives for positive social change. The reflection is concluded with whether the sector—in scholarship and in practice—should reclaim the words of sustainability and resilience or resist their use all together.